Investigating The Arabic Teachers Efficacy to Become a Driving Teacher - Wahdah, Nurul; Hamidah, Hamidah; Mubarak, Mahfuz Rizqi; Nurtianto, Lukman (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This study aims to investigate the efficacy aspects of Central Kalimantan Arabic teachers, such as level, strength, and generality to become a driving teacher. This study used a mixed method by combining qualitative and quantitative designs (concurrent triangulation) by recruiting 19 (nineteen) Arabic teachers at Madrasah Aliyah level from several districts/cities in Central Kalimantan province, Indonesia. The results of this study indicated that the three aspects of the Arabic teachers already have high self-efficacy to become a driving teacher with an average score of 3.79. This is based on their enthusiasm to learn how to use IT in the teaching process and their ability to instill character education and be able to be flexible in dealing with diverse student behavior. However, some difficulties arise from aspects of strength such as difficulties in reflecting and evaluating student-centered learning outcomes and involving the students’ parents.